Russia’s Relations with African Countries in the Light of the Special Military Operation in Ukraine - D. V. Efremenko (Контуры глобальных трансформаций: политика, экономика, право, 2023)
The article analyzes the changes in Russia’s relations with African countries caused by the special military operation (SMO) in Ukraine. From the mid2010s until the beginning of the SMO, these relations were strengthened, which became especially noticeable after the Russia-Africa summit (2019). In addition to the growth of trade and the expansion of military-technical cooperation, a new significant factor in the Russian presence in Africa was the deployment of the activity of private military companies (the “Wagner Group”). In the context of the SMO, cooperation with African states in the areas of trade and economy will go through a stage of painful transformation caused by Western sanctions. A key issue is food security and famine prevention in many countries of the Global South. The modalities of the Russian presence on the African continent will inevitably be determined by the general confrontation between Russia and the countries of the West. In the longer term, African countries may become the beneficiaries of the transformation of the US-centric world order, sufficiently accelerated by the SMO.